Simian Immunodeficiency Virus (SIV)-Specific Chimeric Antigen Receptor-T Cells Engineered to Target B Cell Follicles and Suppress SIV Replication - Haran, Kumudhini Preethi; Hajduczki, Agnes; Pampusch, Mary S.; Mwakalundwa, Gwantwa; Vargas-Inchaustegui, Diego A.; Rakasz, Eva G.; Connick, Elizabeth; Berger, Edward A.; Skinner, Pamela J. (Frontiers in Immunology, 2018)
There is a need to develop improved methods to treat and potentially cure HIV infection. During chronic HIV infection, replication is concentrated within T follicular helper cells (Tfh) located within B cell follicles, where low levels of virus-specific CTL permit ongoing viral replication. We previously showed that elevated levels of simian immunodeficiency virus (SIV)-specific CTL in B cell follicles are linked to both decreased levels of viral replication in follicles and decreased plasma viral loads. These findings provide the rationale to develop a strategy for targeting follicular viral-producing (Tfh) cells using antiviral chimeric antigen receptor (CAR) T cells co-expressing the follicular homing chemokine receptor CXCR5. We hypothesize that antiviral CAR/CXCR5-expressing T cells, when infused into an SIV-infected animal or an HIV-infected individual, will home to B cell follicles, suppress viral replication, and lead to long-term durable remission of SIV and HIV. To begin to test this hypothesis, we engineered gammaretroviral transduction vectors for co-expression of a bispecific anti-SIV CAR and rhesus macaque CXCR5. Viral suppression by CAR/CXCR5-transduced T cells was measured in vitro, and CXCR5-mediated migration was evaluated using both an in vitro transwell migration assay, as well as a novel ex vivo tissue migration assay. The functionality of the CAR/CXCR5 T cells was demonstrated through their potent suppression of SIVmac239 and SIVE660 replication in in vitro and migration to the ligand CXCL13 in vitro, and concentration in B cell follicles in tissues ex vivo. These novel antiviral immunotherapy products have the potential to provide long-term durable remission (functional cure) of HIV and SIV infections.